ANTERIOR MEDIASTINAL TERATOMAS IN INFANTS AND CHILDREN - Stinnett, D. Mitchell (1978)
This report reviews the management of five pediatric patients with anterior mediastinal teratomas, and presents a discussion of symptoms, signs, and operative management of these lesions. Surgical resection was accomplished in all cases, with three of the five patients surviving. The two who died had malignant teratomas that were treated with adjunctive chemotherapy and X-ray therapy. Age at onset appears to be a significant factor in the prognosis of the disease.